Posttraumatic Progressive Vertebral Hemangioma Induced by a Fracture - Kaya Kilic; Emre Unal; Zafer Orkun Toktas; Fugen Vardar Aker; Akın Akakın; Türker Kilic (Case Reports in Surgery)
The authors present an extremely rare case of an aggressive and progressive vertebral capillary hemangioma of the lumbar spine secondary to a trauma. A 40-year-old man who complained of back and leg pain due to a hemangioma of L1 that had begun a year after the fracture of the same vertebra was subsequently operated on. Due to the profuse bleeding, only a subtotal removal was possible. Histopathological diagnosis of the lesion revealed a capillary hemangioma. Postoperative control MRI taken at eight months showed that the lesion and destruction of the L1 vertebra were progressive. A second embolization procedure was performed and this time the hemangioma was totally removed via an anterior approach and corpectomy. Fusion was achieved by Th12-L2 graft and plaque. In the fourteenth year of follow-up, he was symptom-free and radiologically clear of this lesion. We propose that progressive hemangioma is extremely rare and that its cure is possible by total surgical removal of the lesion. This case is the second extradural capillary hemangioma secondary to spinal trauma ever to have been documented in English literature. The emergence of a hemangioma in a fractured vertebra suggests that its pathogenesis can be related to the deviation of the angiogenetic pathways from the normal healing process.